ANALISIS USAHA TERNAK BABI DI KECAMATAN SONDER KABUPATEN MINAHASA - Sarajar, Marsel J; Elly, F H; Wantasen, E; Umboh, S J.K (Universitas Sam Ratulangi, 2019)
ANALYSIS OF PIG FARMING IN SONDERDISTRICTMINAHASA REGENCY. Pigs are developed by the community in Minahasa Regency as a business that supports the livestock farmers' economy. The development of pig farming in this area was carried out in order to increase consumption of animal protein. The problem is that the development of pig farms is not continuous and there have not known factors that influence pork production. This research was conducted with the aim of analyzing production factors that influence the production of pig farming in Sonder District, Minahasa Regency. Survey method was used with direct observation in the field. Sources of data collected are primary and secondary data. Location samples and respondents were determined by using of Cluster Random Sampling metho. Data analysis was conducted by useing descriptive analysis. The results showed that pigs were sold in the form of seeds (starter period pigs) and pork per kg. The price of seeds is Rp. 900,000 per head and the price of pork is Rp. 60,000 per kg. Based on the study results showed that the factors such as feed, labor and cage simultaneously had a significant effect on pig production. Keywords: Pigs, cages, labor, feed